Manfaat Wind Display di Ruang Control Tower Terkait Keselamatan Penerbangan di Bandar Udara Hang Nadim Batam - Dhian Supardam; Ariyono Setiawan; Kukuh Tri Prasetyo (Jurnal Penelitian)
An Air Traffic Controller professionalism is required in the context of efforts to provide Air Traffic Services in order to create the Five Objectives of Air Traffic Service that affect the parameters of a standard of transport services. The problems underlying the need for certainly the very facility that is in control towers in accordance with ICAO document. The purpose of this final task is to understand how the standard tower control room facilities at Hang Nadim Airport Batam in order to improve the quality of Air Traffic Services. Behind the success of the aviation world, especially in the Hang Nadim airport Batam is inseparable from the important role of aviation-related units one of which is a wizard Air Traffic Controller (ATC). ATC has a responsibility in the provision of Air Traffic Services as outlined in the Five Objectives of Air Traffic Service. Behind the success of ATC in the provision of air traffic services can not be separated from the facilities that support their work performance, especially in space where ATC Control Tower provides Air Traffic Services. Batam's Hang Nadim Airport has great potential to become an airport that could benefit Indonesia in the world of aviation. However, it is hampered by the lack of wind facilities in the display space control tower as the air traffic service requirements as listed in Annex 11 ATS chapter 7. Air Traffic Service requirements for information point 7.1.4.3 stating that ATC should provide the information contained wind conditions at the site by looking at the wind display. On this thesis research to try to conduct research on the need for improved facilities and the unavailability of the space control tower is deemed not a standard by the applicable ICAO documents. Associated with an increase in the provision of Air Traffic Services at Hang Nadim Airport Batam